Erythropoiesis-stimulating agents in the management of cancer patients with anemia: a meta-analysis - Liu, Xiaomei; Yan, Zhi; Kong, Dexiao; Zou, Wen; Wang, Jihua; Sun, Dianshui; Jiang, Yuhua; Zheng, Chengyun (Chinese Journal of Cancer Research; Vol 26, No 3 (June 01, 2014): Chinese Journal of Cancer Research, 2014)
Background: Erythropoiesis-stimulating agents (ESAs) are widely used in the management of anemia in cancer patients. Despite their apparent effectiveness, recent studies have suggested that ESAs could result in serious adverse events and even higher mortality. The aim of the current study was to evaluate the benefits and risks of ESAs in the management of cancer patients with anemia using a meta-analysis. Methods: The initial literature search covered Medline, PubMed, Embase, and the Cochrane Center Register of Controlled Trials, and identified 1,569 articles. The final meta-analysis included eight randomized controlled trials (n=2,387) in cancer patients with